The Production of Wheat Pollard Protein Concentrate, a Wheat Milling Byproduct Utilization - Victoria Valentina Sugijanto; Monang Manullang (Jurnal Teknologi dan Industri Pangan, 2001)
ne of protein resources which is not used maximally in Indonesia is wheat pollard. Wheat pollard is a by-product from wheat millings that contains (protein) higher than wheat flour (17.68% compared to 12-13%). Protein concentrate was extracted by alkali and hydrolysed enzymatically.. Alkali method at pH 10 yielded protein value 62.75% and flour yield 17.17%. On the other hand enzymatic hydrolysis method at minute-75 yielded protein value 68.38% and flour yield 48.17%. Amino acid increased after it was made into protein concentrate, for example lysin at the beginning was 8.00 g/100 g sample become 13.00 g/100 g sample (by alkali method) and 19.11 g /100 g sample (by enzymatic hydrolysis method). The highest physicochemical properties derived from enzymatic hydrolysis method were solubility protein (NSI : 95.73%, PDI : 75.21%), water adsorption 57.79%, fat adsorption 80.67%, foam capacity 47.74%, foam stability 84.61%, emulsification capacity 73.59% and strong gelation at 10%. The total result show that enzymatic hydrolysis method is better than extracted alkali method in protein value, yield, amino acid value, and physicochemical properties.